The Perceptions Generations X, Y, and Z Have Toward Work and Industry 4.0 - Rıza Demir; Serpil Aytaç (Sosyal Siyaset Konferansları Dergisi)
This study aims to examine how Generations X, Y, and Z perceive the meaning of work and their approaches toward Industry 4.0. The study has formulated six hypotheses and used a stratified sampling method to apply a questionnaire online involving demographic questions and three separate scales to 435 people. In addition, this paper conducts a scale development study to fill the gap in the literature for a scale related to perceptions toward Industry 4.0. The results show no significant difference to be found among the generations regarding the perceptions toward the meaning of work. However, a weak positive correlation was found between Generation Y’s expectations toward business life and the meaning of work. No difference among the generations was also found regarding knowledge about Industry 4.0, while a significant difference was found between Generations X and Z in terms of their attitudes toward robotic developments.